دراسة كفاءة استخلاص الصبغات النباتية من البنجر الأحمر و الجزر - بليــــلة سليمـــــة; قـــــــديري هنـــاء; كينـــــــــــة فــــاطمة (جامعة الوادي - university of eloued, 2024)
We conducted a study aimed at extracting betalain pigment from red beet (Beta vulgaris L) and carotene pigment from carrot (Daucus carota L) using solvents (methanol, acetone, and distilled water) at concentrations of (99%, 66%, 40%) and volumes of (6ml, 4ml, 2ml) and comparing them. We also estimated the content of both betalain and carotene pigments. Our study revealed that at different stages of maturity (large, medium, and small), acetone solvent extracts carotene pigment and methanol solvent extracts betalain pigment with varying efficiencies. The results showed that the volume of the solvent (acetone and methanol) has a negative effect on the amount of carotene extracted from the carrot; that is, the larger the solvent volume, the lower the extraction efficiency. For betalain pigment, increasing the volume positively affects the quantity extracted, meaning that the larger the volume, the higher the extraction efficiency. We also found that the optimal concentration for extracting betalain and carotene pigments is 66%, which is suitable for efficient extraction regardless of the solvent type. Overall, extraction efficiency depends on the different stages of maturity, the type and volume of the solvent, and the concentration percentage.
Keywords: pigments; Daucus carota; betalain; extraction; Beta vulgaris; carotene